Invitation & Participation: Building the Narrative Environment in Animated Film - Liao, Ying (Auckland University of Technology, 2016)
This thesis explores the methods of building a narrative environment in an animated film to strengthen the participation on the part of the spectator mainly based on the application of Hemingway’s iceberg theory. It analyses Hemingway’s method from different dimensions, discussing its connection to other theories related to eastern philosophies and poetic films. The practical outcome is a short animated film titled Jingle Bells.
Keywords: Narrative; Poetic film; Short animation; 'ma'